THE EFFECTIVENESS OF COMMUNITY-BASED SEA TURTLE MONITORING SUPPORTS HATCHING SUCCESS ON BANDO ISLAND, PIEH ISLAND MARINE PROTECTED AREA - Widhayanti, Arintika; Tyas, Diani Estining; Nugraha, Adiguna Rahmat; Jasilah, Nur; Hanif, Andriyatno; Hamdika, Wahyu; Irfansyah, Rahmat (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
Bando Island is an important part of Pieh Island Marine Protected Area which is a sea turtle nesting habitat in West Sumatra Province. Sea turtle conservation is carried out collaboratively by community groups driving conservation, island customs, and the people of Padang Pariaman Regency. The community groups and the island owners' customary law conduct sea turtle conservation on Bando Island. The purpose of this study was to identify community involvement in sea turtle monitoring activities and analyze the hatching success as an indicator of the effectiveness of community-based sea turtle monitoring on Bando Island. Field surveys were conducted from January 2020 to August 2024. The method used in analyzing research data were quantitative method. The community involvement in sea turtle monitoring consisted of observation, data collection, and reporting. The sea turtle species that landed were green sea turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata). The number of eggs moved to semi-natural relocated nests is 13.123 and the number of hatchlings released is 10.699 green hatchlings and 1.730 hawksbill hatchlings. The effectiveness of community-based sea turtle monitoring can be seen from the discovery of sea turtle tracks that have the potential to find egg nests, the percentage of egg hatching in semi-natural relocated nests was 91,72% indicating optimal hatching power, and hatching success reaching 90.64% which is included in the high category.